Brain nonapeptide levels are related to social status and affiliative behaviour in a cooperatively breeding cichlid fish. Issue 2 (February 2015) - Reddon, Adam R.; O'Connor, Constance M.; Marsh-Rollo, Susan E.; Balshine, Sigal; Gozdowska, Magdalena; Kulczykowska, Ewa
Abstract : The mammalian nonapeptide hormones, vasopressin and oxytocin, are known to be potent regulators of social behaviour. Teleost fishes possess vasopressin and oxytocin homologues known as arginine vasotocin (AVT) and isotocin (IT), respectively. The role of these homologous nonapeptides in mediating social behaviour in fishes has received far less attention. The extraordinarily large number of teleost fish species and the impressive diversity of their social systems provide us with a rich test bed for investigating the role of nonapeptides in regulating social behaviour. Existing studies, mostly focused on AVT, have revealed relationships between the nonapeptides, and both social behaviour and dominance status in fishes. To date, much of the work on endogenous nonapeptides in fish brains has measured genomic or neuroanatomical proxies of nonapeptide production rather than the levels of these molecules in the brain. In this study, we measure biologically available AVT and IT levels in the brains of Neolamprologus pulcher, a cooperatively breeding cichlid fish, using high performance liquid chromatography with fluorescence detection. We found that brain AVT levels were higher in the subordinate than in dominant animals, and levels of IT correlated negatively with the expression of affiliative behaviour. We contrast these results with previous studies, and we discuss the role the nonapeptide hormones may play in the regulation of social behaviour in this highly social animal.